Microfluidic-based production of [68Ga]Ga-FAPI-46 and [68Ga]Ga-DOTA-TOC using the cassette-based iMiDEV™ microfluidic radiosynthesizer - Hemantha Mallapura; Olga Ovdiichuk; Emma Jussing; Tran A. Thuy; Camille Piatkowski; Laurent Tanguy; Charlotte Collet-Defossez; Bengt Långström; Christer Halldin; Sangram Nag (EJNMMI Radiopharmacy and Chemistry, 2023)
Abstract Background The demand for 68Ga-labeled radiotracers has significantly increased in the past decade, driven by the development of diversified imaging tracers, such as FAPI derivatives, PSMA-11, DOTA-TOC, and DOTA-TATE. These tracers have exhibited promising results in theranostic applications, fueling interest in exploring them for clinical use. Among these probes, 68Ga-labeled FAPI-46 and DOTA-TOC have emerged as key players due to their ability to diagnose a broad spectrum of cancers ([68Ga]Ga-FAPI-46) in late-phase studies, whereas [68Ga]Ga-DOTA-TOC is clinically approved for neuroendocrine tumors. To facilitate their production, we leveraged a microfluidic cassette-based iMiDEV radiosynthesizer, enabling the synthesis of [68Ga]Ga-FAPI-46 and [68Ga]Ga-DOTA-TOC based on a dose-on-demand (DOD) approach. Results Different mixing techniques were explored to influence radiochemical yield. We achieved decay-corrected yield of 44 ± 5% for [68Ga]Ga-FAPI-46 and 46 ± 7% for [68Ga]Ga-DOTA-TOC in approximately 30 min. The radiochemical purities (HPLC) of [68Ga]Ga-FAPI-46 and [68Ga]Ga-DOTA-TOC were 98.2 ± 0.2% and 98.4 ± 0.9%, respectively. All the quality control results complied with European Pharmacopoeia quality standards. We optimized various parameters, including 68Ga trapping and elution, cassette batches, passive mixing in the reactor, and solid-phase extraction (SPE) purification and formulation. The developed synthesis method reduced the amount of precursor and other chemicals required for synthesis compared to conventional radiosynthesizers. Conclusions The microfluidic-based approach enabled the implementation of radiosynthesis of [68Ga]Ga-FAPI-46 and [68Ga]Ga-DOTA-TOC on the iMiDEV™ microfluidic module, paving the way for their use in preclinical and clinical applications. The microfluidic synthesis approach utilized 2–3 times less precursor than cassette-based conventional synthesis. The synthesis method was also successfully validated in a similar microfluidic iMiDEV module at a different research center for the synthesis of [68Ga]Ga-FAPI-46 with limited runs. Our study demonstrated the potential of microfluidic methods for efficient and reliable radiometal-based radiopharmaceutical synthesis, contributing valuable insights for future advancements in this field and paving the way for routine clinical applications in the near future.